PENURUNAN TINGKAT DEPRESI KLIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DENGAN LOGOTERAPI MEDICAL MINISTRY DAN TERAPI KOMITMEN PENERIMAAN - Buntar Handayani; Achir Yani Hamid; Mustikasari Mustikasari (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2017)
ABSTRACTDepression is a psychological problem that often occurred in chronic renal failure client and have to get treatment to avoid mental disorder occurred. The purpose of this study was to identify effect of logo therapy medical ministry and acceptance commitment therapy to depression in client with chronic renal failure. This research used quasi experiment design. Sample was 28 respondents in intervention group and 28 respondents in control group. Patients that have up to 10 point in depression scale in hemodialysis unit RS PELNI Jakarta was recruited by consecutive sampling. Variable was analyzed by wilcoxon sign rank test. The result of this research was logo therapy medical ministry and acceptance commitment therapy has significant effect to decrease depression in client with chronic renal failure (p value 0,000). This study also recommends to generally nursing to implement generally intervention, and especially psychiatric nursing in can implement logo therapy and acceptance commitment therapy to avoid or decrease depression in client with chronic renal failure.Keywords: acceptance commitment therapy, chronic renal failure, depression, logotherapy medical ministry